2021
DOI: 10.1021/acs.joc.1c01263
|View full text |Cite
|
Sign up to set email alerts
|

DFT Analysis into the Calcium(II)-Catalyzed Coupling of Alcohols With Vinylboronic Acids: Cooperativity of Two Different Lewis Acids and Counterion Effects

Abstract: The mechanism of the calcium-catalyzed coupling of alcohols with vinylboronic acids has been analyzed by means of DFT computations. This study reveals that the calcium and the boron Lewis acids associate to form a superelectrophile able to promote a pericyclic group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Second, like group 3 compounds, Ca 2+ is a strong Lewis acid, especially when coordinated to weakly binding ligands such as fluorides (F – ), triflates (OTf – ), bistriflimides (NTf 2 – ), or 1:1 bistriflimide/hexafluorophosphate (PF 6 – ) counterions. These Ca 2+ salts form Lewis acid/base adducts to activate otherwise weakly electrophilic compounds such as alcohols, carbonyls, olefins, and boronic acids for subsequent coupling with nucleophilic reagents, notably also with relatively high tolerance to air and moisture. In our recent reports, we employed Ca 2+ salts for the first time to activate a different class of compoundssulfur­(VI) fluorides. , …”
Section: Introductionmentioning
confidence: 99%
“…Second, like group 3 compounds, Ca 2+ is a strong Lewis acid, especially when coordinated to weakly binding ligands such as fluorides (F – ), triflates (OTf – ), bistriflimides (NTf 2 – ), or 1:1 bistriflimide/hexafluorophosphate (PF 6 – ) counterions. These Ca 2+ salts form Lewis acid/base adducts to activate otherwise weakly electrophilic compounds such as alcohols, carbonyls, olefins, and boronic acids for subsequent coupling with nucleophilic reagents, notably also with relatively high tolerance to air and moisture. In our recent reports, we employed Ca 2+ salts for the first time to activate a different class of compoundssulfur­(VI) fluorides. , …”
Section: Introductionmentioning
confidence: 99%
“…The meta -hybrid M062X functional was successfully used for studies of catalytic reactions involving calcium complexes. 36 The combination of the M062X functional and DGDZVP basis set earlier predicted correctly the thermodynamics and kinetics of reactions of 14 group complexes. 37 The resulting catalytic model (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…It has previously been shown that Ca(NTf 2 ) 2 and PF 6 salts underwent anion metathesis to form KNTf 2 and Ca(NTf 2 )PF 6 . 20 The latter salt, more Lewis acidic than Ca(NTf 2 ) 2 and displaying two binding sites available on the calcium center, was reported to activate a wide range of substrates such as cyclopropanes, [39][40] carbonyl compounds, [41][42] alcohols, [43][44][45][46][47][48] alkenes 49,50 or more recently sulfonyl 51,52 fluorides. 20,28,53 Ca(NTf 2 )PF 6 , whose Lewis acidity has been evaluated by the Childs method, 41 has also been associated with hexafluoroisopropanol as the solvent and the resulting system shown by Gandon and Leboeuf to be highly active in various transformations including Aza-Piancatelli, 54,55 hydroarylation, 56 or hydroamidation 57 or hydroacyloxylation 58 reactions.…”
Section: Resultsmentioning
confidence: 99%